2007
DOI: 10.1152/ajpheart.01217.2006
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase and nitric oxide synthase dependence of cutaneous reactive hyperemia in humans

Abstract: Medow MS, Taneja I, Stewart JM. Cyclooxygenase and nitric oxide synthase dependence of cutaneous reactive hyperemia in humans. Am J Physiol Heart Circ Physiol 293: H425-H432, 2007. First published March 16, 2007; doi:10.1152/ajpheart.01217.2006.-We tested the hypothesis that cyclooxygenases (COXs) or COX products inhibit nitric oxide (NO) synthesis and thereby mask potential effects of NO on reactive hyperemia in the cutaneous circulation. We performed laser-Doppler flowmetry (LDF) with intradermal microdialys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
57
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(69 citation statements)
references
References 35 publications
(54 reference statements)
8
57
1
3
Order By: Relevance
“…The results were substantiated by the study of Zhao et al, who assessed the concentration of NO in the microdyalisate using a NO selective amperometric electrode (Zhao et al, 2004). Other studies have confirmed an involvement of NO in the PRH response (Bingelli et al, 2003;Medow et al, 2007), yet it seems only of minor importance compared to other mechanisms. A conceivable speculation has been made by Medow et al: they propose that the COX inhibition unmasks the NO dependence of PRH in human skin (Medow et al, 2007).…”
Section: Human Skin Microcirculation and The Endothelium: Impact Of Nmentioning
confidence: 79%
See 3 more Smart Citations
“…The results were substantiated by the study of Zhao et al, who assessed the concentration of NO in the microdyalisate using a NO selective amperometric electrode (Zhao et al, 2004). Other studies have confirmed an involvement of NO in the PRH response (Bingelli et al, 2003;Medow et al, 2007), yet it seems only of minor importance compared to other mechanisms. A conceivable speculation has been made by Medow et al: they propose that the COX inhibition unmasks the NO dependence of PRH in human skin (Medow et al, 2007).…”
Section: Human Skin Microcirculation and The Endothelium: Impact Of Nmentioning
confidence: 79%
“…Other studies have confirmed an involvement of NO in the PRH response (Bingelli et al, 2003;Medow et al, 2007), yet it seems only of minor importance compared to other mechanisms. A conceivable speculation has been made by Medow et al: they propose that the COX inhibition unmasks the NO dependence of PRH in human skin (Medow et al, 2007). The results could strengthen the hypothesis on the crosstalks between various endothelial vasodilators in human skin.…”
Section: Human Skin Microcirculation and The Endothelium: Impact Of Nmentioning
confidence: 82%
See 2 more Smart Citations
“…7,28 Indeed, the mechanisms that have been suggested to contribute to the process of postocclusive hyperemic responses include increase in the vasodilator NO following increases in shear stress associated with the increased blood fl ow after an ischemic period, 29 and likely the accumulation of metabolic vasodilators such as adenosine and prostaglandins. 30 The selection of the arterial occlusion time at 60 s rather than 5 min, which is typically used in most ischemic challenges in adult studies, was dictated by the priority of ensuring the children's comfort during testing, thus preventing motion-induced artifacts and preserving the validity of the tests.…”
Section: Resultsmentioning
confidence: 99%